The sound environment and soundscape preservation in historic city centres—the case study of Lhasa. (July 2015) - Huang, Lingjiang; Kang, Jian
The historic city centre of Lhasa has preserved special types of historic and cultural heritage for various reasons, including strong religious beliefs, preservation policy, and slow globalisation. In addition to visual cultural heritage, the sound environment represents a cultural heritage that requires preservation. This paper presents an analysis of the sound environment of Lhasa's historic city centre based on field investigations and soundwalk measurements during the tourism high season. First, Lhasa's historic urban form and cultural background are introduced. Second, the relationship between the historic urban space and the sounds is investigated according to the sound sources. The sound taxonomy and the cultural meanings of these sounds are examined and identified. Third, the sound environments are evaluated from the perspectives of sound sources and sound changes with time and frequency. The sound pressure level is found to be high in the historic centre, which might affect the sound sources associated with cultural identities. Additionally, significant variations within the centre—both spatial and temporal—that are indentified in the sound pressure levels and spectrums are reflected in the characteristics of local daily life and social activities. Finally, comparisons are made between Lhasa's historic centre and a number of other historic centres and squares. Possible implications of the results and principles of soundscape preservation are also discussed, based on the case study of Lhasa.